SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM UPAYA MEMBANTU GURU MENGATASI KESULITAN MENGAJAR DI SMP - Lucy Evriani; Rambat Nur Sasongko; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
The problem of this research is how academic supervision of the principal in helping teacher to overcome teaching difficulty at junior high school number 1 south Bengkulu. The method of this research was qualitative.research. The data were taken by conducting by personal interview, observations and documentation study. The data analysis used qualitative technique. The result of this study showed that (1) most of the teachers who were supervised had been fulfill aspect in academic supervision (2) academic supervision of principal used non directive and collaborative approach (3) headmaster used individual and group technigue in academic supervision (4) steps in academic supervision had been done by the principal.